Market Research on The Global Bioengineering Analytics and Software Market - Malyshev, Viktor; Kovalenko, Viktoriia; Gab, Angelina; Sherman, Zoia; Brindak, Danylo (International Journal of Basic and Applied Sciences, 2025)
The purpose of this study was to analyse current trends and prospects of the global bioengineering analytics and software market. The study identified the key factors that determine the growth of the bioengineering analytics and software markets, as well as their effects on medical and economic processes. The principal findings of the study revealed substantial changes in the global bioengineering analytics and software market. The analytics market, which was worth USD 9 bn in 2022, showed an annual growth rate of 7.6%, which will reach USD 16.3 bn by 2030. The services segment in this area accounts for 54.8% of revenue, highlighting the significance of outsourcing. Predictive analytics, which showed growth of 9% per year, is one of the most promising areas. As for the software market, it was worth USD 16.32 bn in 2022 and is expected to increase to USD 44.72 bn by 2030, with an average annual growth rate of 12.9%. Cloud computing, specifically, revealed considerable growth, increasing its share from USD 9.3 bn in 2023 to USD 25.8 bn in 2033. Investments in bioengineering software are taking place mainly in China and India, where the highest growth rates are 8.3% and 10.3%, respectively, as well as in the United States of America. These findings suggest the rapid growth of the global bioengineering analytics and software market, which highlights their critical contribution to the development of medical services and healthcare innovations, creating new opportunities for improving medical and economic processes.